Antihyperuricemia of Lemongrass Extract (Cymbopogon citratus) on Male Mice with Potassium Oxonate and Chicken Liver Juice Induced - Fadhila, Rizky; Nainggolan, Hotlina (Research and Social Study Institute, 2024)
Background: Hyperuricemia is a pathological condition characterized by increased blood uric acid levels exceeding 7 mg/dL. The use of medicinal plants for managing hyperuricemia has garnered significant attention.Aims & Methods: This study aims to evaluate the anti-hyperuricemic effect of lemongrass extract (Cymbopogon citratus) in a hyperuricemia model using 18 Deutsche Denken Yoken (DDY) mice induced with potassium oxonate and chicken liver juice. Lemongrass simplicia was extracted by maceration using 96% ethanol. Test animals were induced with hyperuricemia by administering chicken liver juice at a dose of 0.5 mL/20 g body weight (BW) for seven consecutive days and potassium oxonate at a dose of 250 mg/kg BW on the eighth day. The test animals were divided into six test groups, namely group 1 was the normal; group 2 was the negative control; group 3 was the positive control (allopurinol at 13 mg/kg BW); groups 4 – 6 were treatment lemongrass extract at doses of 350, 700, and 910 mg/kg BW, respectively.Result: The results showed that group 6 mice statistically significantly reduced uric acid levels (p = 0.001, p < 0.05). Cymbopogon citratus extract effectively reduces uric acid levels and holds substantial potential as a uric acid-lowering agent, supporting its empirical use in managing hyperuricemia.